Crustacean Female Sex Hormone From the Mud Crab Scylla paramamosain Is Highly Expressed in Prepubertal Males and Inhibits the Development of Androgenic Gland - Liu, An; Liu, Jing; Liu, Fang; Huang, Yiyue; Wang, Guizhong; Ye, Haihui (Frontiers in Physiology, 2018)
Recently, the crustacean female sex hormone (CFSH), which is considered a female-specific hormone, has been shown to play a crucial role in female phenotypes in crustaceans. In this study, two transcripts (Sp-CFSH1 and Sp-CFSH2) encoding the same CFSH precursor, were cloned from the mud crab Scylla paramamosain. Homology and phylogenetic analysis showed that CFSHs were homologous to interleukin-17 (IL-17) and highly conserved among brachyuran crabs. PCR analysis revealed that Sp-CFSH was expressed exclusively in the eyestalk ganglion of both prepubertal males and females, and surprisingly, the abundance of Sp-CFSH transcripts detected in the males were not significantly different from that of the females (P > 0.05). In addition, mRNA in situ hybridization showed that Sp-CFSH was localized in the X-organ of the male eyestalk ganglion. During the development of the androgenic gland (AG), the level of Sp-IAG mRNA in AG remained at low levels from stage I to II (early stage) but had a significant increase at stage III (mature stage). In contrast, the level of Sp-CFSH transcripts in the eyestalk ganglion was high in the early stage but extremely low in the mature stage. To investigate the potential function of CFSH in male S. paramamosain, the recombinant protein (~20 kDa) was expressed in Escherichia coli and was subsequently added to AG explants in vitro. It was demonstrated that rCFSH significantly reduced the expression of Sp-IAG in the AG explants at a concentration of 10-6 M (P < 0.05). In conclusion, our study provides the first piece of evidence that shows CFSH from the eyestalk ganglion acts as a negative regulator inhibiting the development of AG in crustaceans.